Monetarism - Thomas Mayer; Patrick Minford (University of California, Department of Economics, 1995)
Monetarism is hard to define because it is not the doctrine of a school that is sharply differentiated from the rival Keynesian and new classical schools. While some ecconomists are clearly monetarists, others take intermediate positions that make it more or less arbitrary whether to call them monetarists. The basic theoretical propositions of monetarism, that changes in the quantity of money (defined as currency plus at least checkable deposits) play the central role in the determination of nominal income. differs only in degree from the view held by most Keynesians that changes in th~e quantity of money are a major (and in the long run the dominant) determinant of changes in nominal income. There is little disagreement between Keynesians, monetarists and new clac+A economists about long run equilibrium. But while new classical economists think that this equilibrium is reached rapidly, and Keynesians think it is reached slowly, monetarists take an intermediate position. That is an important difference because many policy questions relate to this intermediate run. To be sure, much of the monetarist research strategy focuses on changes in the sdpply of and demand for money, while the Keynesian strategy is to look also at the propensity to consume, the marginal efficiency of investment, government expenditures and net exports. But this difference relates only to the way of proceeding with research, and not directly to how the economy functions. There is greater disagreement on policy. Some monetarists agree with K~ynesians, that - in principle - fiscal policy can have a significant effect on nominal income, but deny that in practice it has a large effect. Others deny that even in principle fiscal policy has a significant effect on income. While hard-core monetarists believe that the money supply should grow at a fixed rate, other merely want the growth rate of money to be stable, a position not so different from that of some Keynesians who oppose %ne-tuning"". There are several major sources of monetarism. One is the work of MiRon Friedman (1 912-) (see Friedrnan, 1956, l969), a leader of the Chicago school, and Anna Schwartz (1915-). The other is the work of Karl Brunner (1916-89) and Allan Meker (1 928 -).(See Bwnner and Mettzer, 1989; 1993) Brunner and Meltzer''s work temds to focus somewhat more on theoretical issues than does Friedman''s. For a time
Keywords: 330